New explorations in Chinese theoretical syntax studies in honor of Yen-Hui Audrey Li - Simpson, Andrew, 1962-; Li, Yen-hui Audrey, 1954- (Linguistik aktuell ;, 2022)
"This volume brings together 19 cutting edge studies written by some of the most prominent linguists working on Chinese formal syntax, as a Festschrift volume dedicated to Yen-Hui Audrey Li. The contributions to the volume address a wide range of issues currently developing in the field of Chinese syntax, grouped into five thematic sections on the structure of lexical and functional projections, modal verb syntax, syntax-semantics interactions, the syntax and interpretation of particles, and the acquisition of syntactic structures. With its rich descriptive content sourced from different varieties of Chinese, and its theoretical orientation and analyses, the book provides an important new resource both for researchers with a primary interest in Chinese and other linguists interested in discovering how properties of Chinese can inform the analysis of other languages"--